Knowledge, Attitude and practice of late adolescent girls on reproductive health: A focus on menstruation in Khwopa college of Bhaktapur. - TuiTui, Roshani Laxmi (2006)
ABSTRACT: This study represents the study of the Knowledge, Attitude and practice (KAP) of reproductive health (RH) among 102 adolescents girls of 15-19 years of age in Khwopa College Bhaktapur. The main objective is to assess their current level of knowledge on RH and menstruation and their attitude and practice of menstrual hygiene. Self administered structured questionnaire was used to collect the data based on stratified systematic random sampling technique. The karl Pearson Product Moment Correlation Coefficients with one tailed test has been used to identify the association of birth order, education of parent and occupation of parent with knowledge of puberty and menstruation hygiene. This statistical technique is appropriate for analyzing association between the dichotomous variable. Bivariate analysis has been carried out to identify the relationship between independent and dependent variables. Result: Most of the respondents are in age group 17 years and the mean age of respondent is 17.5 years. Most of respondents have knowledge on meaning of RH (91.8%) and menstruation (97.9%). The common sources of getting information of RH are course book (95.8%), TV (43.2%), Radio (41.1%), and magazine (34.7%). The most frequently observed pubertal changes are breast enlargement (74.7%) , height increase (60%), weight gain (57.9%), attraction to opposite sex (49.5%). The common person for sharing pubertal feeling is mother (66.3%),friend (62.1%) and sister (45.3%). Almost ninety percent get information about menarche before they get menstruation and the most reliable person is mother (65.3%) and friend (40%), The common source is book (89.5%). All respondents experienced menstruation at time of the survey. The mean age of menstruation is 13.5 years. There are varieties of attitudes and practices towards menstruation in the society. The common practice is to keep them in separate room without exposure to sunlight (46.3%) and the duration is mostly 12 days (37.9%). Most of the respondents (70.5%) felt necessity of menstrual hygiene. The most frequently used pad is old clean cloth (86.3%) and sanitary pad (31.6%). The frequency of changing pad is two times a day (42.1%) and 85.3 percent reported to re-use the pad and the materials used for cleaning are soap and water (90.5%) and they dry pad on direst sunlight (74.4%). Almost 93 percent clean the genitalia in between pad change and 25.6 percent only adopt anterior to posterior method. Almost all respondents (95.8%) faced different during menstruation. The most common problems are backache (56.8%), weakness (47.4%), dysmenorrhoea (46.3), bleeding disorder (20.9%), and lethargy (17.9%). The frequently consulted person is mother (77.9%) and sister (45.3%) whereas the doctor is the least consulted person (14.7%). Remedial measures for menstrual problem are taking rest and sleep (66.3%), taking hot water bag (25.3%), and taking medicines (22.1%). Most of the respondents (94.75) feel that they need further education on RH. The dependent variable in the bivariate analysis is knowledge on meaning of puberty and menstruation, practice of menstrual hygiene ( frequency of taking bath, frequency of changing pad, type of pad used, way of cleaning and drying pad, and way of cleaning genitalia). The independent variable considered includes birth order of the respondents, education of father and mother and occupation of father and mother. Among the variables being investigated , association of birth order and education of mother with the knowledge on puberty is significant at 0.01 level. Birth order is negatively and the education of mother is positively associated with the knowledge on puberty among adolescents. Similarly, association of occupation of father with knowledge on menstruation is positive, that is significant at 0.01 level. Association of education of father and occupation of mother with kind of pad used during menstruation is negative that are significant at 0.05 and 0.01 level respectively. Adolescents with lower education status parents tend to use old clean cloth and the purchasing of sanitary pad depends upon education of father and the occupation of mother. Education of mother and occupation of father is also significantly correlates with frequency of pad change during menstruation. Birth order is significant with cleaning practice of used pad. It has no effect of education and occupation of the parents. Similarly, education of mother, occupation of mother and occupation of father is also significantly correlates with the ways of washing genitalia and maintaining good hygiene during menstruation. Conclusion: Further research is needed on menstruation and adolescent girls should teach on proper menstrual hygiene.